STRESS CONCENTRATION FACTOR OF NOTCHED HYBRID RECYCLED CARBON COMPOSITE (Journal of Transport System Engineering, 2024)
Recycled carbon fiber (r-CF) holds significant promise for reducing both production waste and costs associated with its manufacturing, which is characterized by high energy intensity. However, its full potential remains untapped due to limited understanding of its mechanical behavior, particularly concerning stress concentration factors in notched recycled carbon fiber-reinforced polymer (r-CFRP). This study is dedicated to investigating the mechanical properties of r-CFRP and characterizing the tensile behavior of notched composites. Additionally, it explores new functionalities of r-CF and introduces a methodology for correlating strain fields obtained from digital image correlation (DIC) with stress concentration factors (SCF). Three types of composite materials—glass fiber-reinforced polymer (GFRP), r-CFRP, and hybrid GFRP/r-CFRP—are included in this research, encompassing both unnotched and notched composites subjected to tensile tests. DIC was chosen as the strain field measurement technique for its enhanced accuracy and speed compared to conventional methods such as strain gauges. The analysis revealed that GFRP exhibits the highest Young's Modulus (E) at 19.64 ± 0.72 MPa, followed by hybrid GFRP/r-CFRP at 15.22 ± 0.99 MPa and r-CFRP at 12.97 ± 0.48 MPa. For notched composites, this study analyzed SCF and strength retention for each material. r-CFRP exhibits the highest SCF at 1.57 and the lowest strength retention at 63.70%, signifying its high notch sensitivity. However, the incorporation of r-CFRP in hybridization with GFRP enhances the SCF to 1.46 and increase the strength retention to 81.02%, which was the highest among the three laminates. These results demonstrate that r-CFRP has the potential to mitigate stress concentration, making it an ideal material for producing notch-insensitive hybrid glass fiber composites.
Keywords: Recycled Carbon Fiber; Stress Concentration Factor; Digital Image Correlation, Notched Composite